GLOBALIZACIÓN, LIBRE COMERCIO Y GÉNERO - Freyre Valladolid, Mayela (2004)
The globalization process presents strong and contradictory patterns. On one side, ir incorporates the world population into the benefits of information, production and technology innovations, and, in the other side, it excludes great groups of the same world population that cannot obtain those benefiis, resulting in more inequalities, inequiiies, unemployment and poverty. The most important issue of the globalization andfree trade process is grounb without employment. This is no more than what surfaces of a constant process of setting aside large population groups, which cannot accede to growth opportunities. • Poverty not only has increased, but also has meant a kind of poverty 's feminization, as women are the more affected by the work flexibility processes and improvement of the competitive advantage of business. This has put in evidence the iraditional paradigm crises of development and growth. The concept of development not only pertains to the accumulaiion, industrialization and consumpiion, but it should be understood in its concept of equity and sustainability.